Teledetection as an instrument for the glacier analysis in high-mountain ecuadorian highland environments (Revista Electrónica REDINE, 2017)
Global warming is a climatic phenomenon with affects of different nature on a global scale. One of its effects is the increase in the atmospheric temperature, which directly affects the melting of the ice masses that make up the glaciers, especially in the high tropical mountain. In this context, the present study aims to identify and analyze the temporal changes that have presented three glaciers located in the Ecuadorian Andes. To develop the study, Geographic Information Systems software and a set of satellite images of different dates were used to obtain data through the application of the Normalized Difference Snow Index (NDSI). As a result it was found that the glaciers presented a significant decline and decrease in surface area, contracting significantly towards sectors of higher elevation.
Keywords: global warming; climate change; glaciers